2020
DOI: 10.1007/s13197-020-04400-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-obesity properties of local chilies varieties in Malaysia

Abstract: Obesity is a serious health concern as it may initiate common chronic diseases. Chili pepper is an important spice that brings spiciness and commonly used in cuisines. However, the antioxidant and anti-obesity properties of chili varieties in Malaysia has not yet been fully investigated. Therefore, this study aimed to determine the antioxidant (content and activity) and anti-obesity properties of five different varieties of local chili peppers. The antioxidant activities of the extracts were determined through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…A previous experiment reported that the ABTS in pepper varied from 89.25 to 141.25 μmol TE/g when extracts were made from seeds, and from 17.17 to 97.40 μmol TE/g for pulp extracts (Sora et al, 2015). On the other hand, the samples evaluated in a different study showed elevated TAC when the extracts were made with pulp (Huei et al, 2020), reporting values of TAC from 91.95 mg/mL to 0.4 mg/mL for the highest and the lowest concentration in samples, respectively. Such results have similarity with the samples analyzed in the current experiment, but in our case the essay was carried out with pulp samples.…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 95%
See 1 more Smart Citation
“…A previous experiment reported that the ABTS in pepper varied from 89.25 to 141.25 μmol TE/g when extracts were made from seeds, and from 17.17 to 97.40 μmol TE/g for pulp extracts (Sora et al, 2015). On the other hand, the samples evaluated in a different study showed elevated TAC when the extracts were made with pulp (Huei et al, 2020), reporting values of TAC from 91.95 mg/mL to 0.4 mg/mL for the highest and the lowest concentration in samples, respectively. Such results have similarity with the samples analyzed in the current experiment, but in our case the essay was carried out with pulp samples.…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 95%
“…Literature has reported that FRAP (Benzie & Strain, 1996) and ABTS (Re et al, 1999) methods are effective to determine antioxidant activity. These methods are convenient and easy to use, giving reliable results (Huei et al, 2020;Sora et al, 2015).…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 99%
“…40 En un estudio realizado en ratas Wistar con obesidad inducida, la administración de una dieta alta en grasas adicionada con 41 En ensayos in vitro, reportaron que los extractos etanólicos en concentraciones de 3.61 mg/mL y 2.71 mg/mL de especies de C. annuum y C. frutescens, respectivamente, redujeron la concentración de adipocitos 3T3-L1, además, inhibieron el nivel de lípidos en los adipocitos hasta en un 69 % y 63 %, respectivamente; los extractos tuvieron la capacidad de inhibir la actividad de la lipasa pancreática, tratamiento similar con Orlistat, medicamento utilizado en el tratamiento del control de peso. 42 La administración de 3.2 g/d de una formulación alta en grasas, adicionada con 200 mg/kg de peso de extracto de capsantina, disminuyó el peso corporal en ratones C57BL/6J con obesidad inducida en un 27.5 %, además, la administración de la dieta alta en grasas con capsantina redujo (p<0.05) los niveles séricos de triglicéridos, colesterol y LDL, comparado con aquellos alimentados únicamente con la dieta alta en grasas. 43 La capsaicina es capaz de unirse a proteínas que activan neuronas sensoriales por medio de estímulos térmicos, vinculándose a la termogénesis; también presenta efecto sobre algunas proteínas implicadas en el metabolismo de lípidos y carbohidratos, lo que permite regular los niveles de hormonas supresoras del apetito 44 , además, tiene la capacidad de aumentar o reducir la expresión de genes como 7-α-hidroxilasa (CYP7A1), del transportador de ácido biliar ileal (ASBT) y de la proteína ileal de unión al ácido de la bilis (IBABP), implicados en la homeostasis de colesterol, mejorando el metabolismo endógeno de esteroles.…”
Section: Control De Peso Y Actividad Hipolipemianteunclassified
“…Chili is used varies such as for instant seasoning mix, chili sauce [11,14], or filled chocolate [15]. In addition, chili can be known to have antioxidants [16] and anti-obesity [17], bio pesticides [18], tea [19]. The need for fresh chili is increasing along with the increasing in Indonesia's population.…”
Section: Introductionmentioning
confidence: 99%